The Pristine survey II: A sample of bright stars observed with FEROS1. Issue 6 (10th July 2017) - Caffau, E.; Bonifacio, P.; Starkenburg, E.; Martin, N.; Youakim, K.; Henden, A. A.; González Hernández, J. I.; Aguado, D. S.; Prieto, C. Allende; Venn, K.; Jablonka, P.
Abstract : Extremely metal‐poor (EMP) stars are old objects formed in the first Gyr of the Universe. They are rare and, to select them the most successful strategy has been to build on large and low‐resolution spectroscopic surveys. The combination of narrow‐ and broad‐band photometry provides a powerful and cheaper alternative to select metal‐poor stars. The ongoing Pristine Survey is adopting this strategy, conducting photometry with the Canada France Hawaii Telescope MegaCam wide‐field imager and a narrow‐band filter centered at 395.2 nm on the Ca II‐H and ‐K lines. In this paper, we present the results of the spectroscopic follow‐up conducted on a sample of 26 stars at the bright end of the magnitude range of the Survey ( g ⩽15), using FEROS at the MPG/ESO 2.2‐m telescope (manufactured by Zeiss, Oberkochen, Germany). From our chemical investigation on the sample, we conclude that this magnitude range is too bright to use the Sloan Digital Sky Survey (SDSS) g r i bands, which are typically saturated. Instead, the Pristine photometry can be usefully combined with the AAVSO Photometric All Sky Survey (APASS) g r i photometry to provide reliable metallicity estimates.